KAJIAN TERHADAP TUJUAN FILOSOFIS DAN REALITAS LEMBAGA NEGARA INDEPENDEN DI INDONESIA - Fahrozi, Muhammad Helmi (Faculty of Law, Parahyangan Catholic University, 2024)
The establishment of independent state agencies in Indonesia represents efforts to reform and restructure the government in accordance with the mandates of constitutional amendments. These institutions are envisioned to embody the ideals of reform, with high expectations placed on their independence. However, in practice, independent state institutions often face challenges, including issues with performance and accountability, raising fundamental questions about their primary purpose and role within Indonesia's constitutional framework. This study seeks to examine the objectives behind the formation of independent state institutions, their implementation, and their contribution to the constitutional system in Indonesia. Using a normative juridical method with legislative and historical approaches, the research highlights the philosophical values underpinning these institutions. The findings emphasize that their primary purpose is to act as instruments for advancing democracy. However, this role must align with principles of accountability and transparency to the public. Without these principles, independent state institutions risk becoming dependent on other state powers, as observed in cases involving institutions like the Corruption Eradication Commission/KPK. Moreover, persistent challenges, such as legal product controversies involving the General Election Commission/KPU and Indonesian Financial Services Authority/OJK, underscore the need for improved governance and openness to fulfill their intended role effectively.